Markets, Clans, and Arbitrage: A Participant‐Observation Study of "Coopetition" Among Baseball Ticket Scalpers. Issue 3 (26th February 2018) - Bozeman, Barry; Taggart, Gabel
Abstract : We report on a participant‐observation study of baseball ticket scalpers at Chase Field in Phoenix, Arizona. Ours is a study of the market behavior of individuals working in clans. We focus on the social organization of clans and, particularly, how scalpers establish territories and engage in cooperative behavior while, at the same, time competing aggressively. The clans govern transactions not according to straightforward economic exchange or by formal rules and regulation emanating from legitimate authority, but rather through shared goals and shared values, with behavior expectations grounded in familiarity, common history, and mutual trust. During conversations with scalpers, we determined that a few of them, but not the majority, consult StubHub on a real‐time basis to help them determine their spot market ticket prices. Conclusion: The rise of Internet secondary markets for tickets may ultimately have adverse consequences for street vendors, but at present, it seems more advantageous than disadvantageous.